PERBANDINGAN KADAR LEUKOSIT DARAH PADA PASIEN APENDISITIS AKUT DAN APENDISITIS PERFORASI DI RSUD MEURAXA BANDA ACEH - Mohammad Hendro Mustaqim; Aya Sophia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Appendicitis is defined as inflammation of the appendix vermiformis (worm sac) which is the most common surgical emergency in children and young adults with abdominal pain. Appendicitis is thought to be caused by obstruction of the appendix lumen by faecalith, faecal stasis, lymphoid hyperplasia or caecal neoplasms and various infections by pathogens. This study aims to determine the comparison of blood leukocyte levels in acute appendicitis and perforated appendicitis in Meuraxa Hospital, Banda Aceh. This type of research is a retrospective study survey research with cross sectional research design. Retrieval of data from medical records. The number of samples used 89 people consisting of 56 patients with acute appendicitis and 33 patients with perforated appendicitis. Data analysis using Independent sample t-test. The mean value of blood leukocytes in patients with acute appendicitis was 10,741.8 cells/mm3 and perforated appendicitis was 20,023.6 cells/mm3. The results of this study showed the p-values of acute appendicitis and perforated appendicitis patients were P = 0.239 and P = 0.749, respectively. Independent test sample t test obtained t test statistics of -11,963 with P 0,001. There is a difference between blood leukocyte levels in patients with acute appendicitis and perforated appendicitis.Keywords: Acute appendicitis, perforated appendicitis, blood leukocytesÂ